2018
DOI: 10.7554/elife.39270
|View full text |Cite
|
Sign up to set email alerts
|

Oldest skeleton of a fossil flying squirrel casts new light on the phylogeny of the group

Abstract: Flying squirrels are the only group of gliding mammals with a remarkable diversity and wide geographical range. However, their evolutionary story is not well known. Thus far, identification of extinct flying squirrels has been exclusively based on dental features, which, contrary to certain postcranial characters, are not unique to them. Therefore, fossils attributed to this clade may indeed belong to other squirrel groups. Here we report the oldest fossil skeleton of a flying squirrel (11.6 Ma) that displays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 94 publications
0
37
0
Order By: Relevance
“…Although it is not statistically significant, the presence of the Sciurini in the Palaearctic could be traced back to the early Miocene. In our reconstruction, several Pteromyini lineages dispersed into the Palaearctic from the Indomalayan realm during the late Miocene, although there is fossil evidence that some other lineages of this tribe were present in Europe from the Oligocene onwards (Heissig 1979a,1979b, De Bruijn 1999, Dawson 2003, Heissig 2003, Gómez Cano et al 2014, Casanovas‐Vilar et al 2018). In fact, other research has suggested a Palearctic origin of Pteromyini (Lu et al 2013).…”
Section: Resultsmentioning
confidence: 72%
“…Although it is not statistically significant, the presence of the Sciurini in the Palaearctic could be traced back to the early Miocene. In our reconstruction, several Pteromyini lineages dispersed into the Palaearctic from the Indomalayan realm during the late Miocene, although there is fossil evidence that some other lineages of this tribe were present in Europe from the Oligocene onwards (Heissig 1979a,1979b, De Bruijn 1999, Dawson 2003, Heissig 2003, Gómez Cano et al 2014, Casanovas‐Vilar et al 2018). In fact, other research has suggested a Palearctic origin of Pteromyini (Lu et al 2013).…”
Section: Resultsmentioning
confidence: 72%
“…2017; Casanova‐Vilar et al. 2018), and a multivariate PGLS regression shows that arborealists and gliders are significantly different (Table 1). The phylomorphospaces demonstrate that gliders have evolved toward a region of multivariate morphospace (i.e., the upper right quadrant in both PCAs) that is largely unoccupied by taxa of additional locomotor modes (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…In the Miopetaurista plot, the Petaurista species are highlighted because Miopetaurista and Petaurista are considered closely related sister taxa (Casanovas‐Vilar et al. 2018; Supplementary Results).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All this evidence suggests a woodland/shrubland biome [ 50 ] (Additional file 5 : Figure S4). Nonetheless, the record of the aquaphilous tragulid Dorcatherium naui [ 60 ], flying squirrels [ 61 ] and arboreal dormice at ACM/C5-D1 indicate that permanent water masses (palustrine areas or streams) and forests were also present in this phase. Accordingly, our results are consistent with more open, mosaic environments in phase III, although they may have been interspersed with restricted gallery forests, which would have provided a denser tree cover and preserved some subtropical plant elements—contrasting with the predominant vegetation of the nearby areas.…”
Section: Discussionmentioning
confidence: 99%